Effects Of Mount Agung Eruption On Chemical Composition And Physical Characteristics Of Bali Cattle Ration Fed In Talibeng Evacuation Zones Sidemen District Karangasem Regency - I. P. G. D, Widiarta; Suarna, I W.; Suryani, N. N. (Jurnal Peternakan Tropika, 2019)
Mount Agung eruption, August to December 2017, caused bali cattle to be evacuated. This aims of this study to compare the quality of bali cattle ration according to its chemical composition and physical characteristics before and after in evacuation zones. The first step is survey, conducted on January to April 2018 to the farmers to obtain information regarding the botanical composition of ration before and after in evacuation zones as well as sampling feed ingredients (forages and concentrates). The second step is analysis in the laboratory from May to June 2018. Ration sample was made according to observation at evacuation zones and the tabulation of questionnaire result data. The research variables were chemical compositionof ration ie: dry matter (%), organic matter (%), crude protein (%), crude fiber (%), ether extract (%) and gross energy (kcal/kg) and physical characteristics ie: bulk density (g/ml), water holding capacity (%), water solubility (%) of the ration. Study showed that the quality of bali cattle ration given before was better than after at the evacuation zones. Protein and energy content of ration before in evacuation zones were 17.94% and 4027 kcal/kg respectively and 8.85% and 3790 kcal/kg after evacuation zones. Physical characteristics of ration which includes bulk density, water holding capacity, and water solubility are higher before in evacuation zones. Keywords: chemical composition, bulk density, water holding capacity, water solubility